Estimation of UTS from small punch test using an improved method. (December 2022) - Pandey, Aishwary Vardhan; Karthik, V.; Shaik, Abdul Rahman; Kolhatkar, Ashish; R., Divakar
Abstract: Small punch test is a promising method for evaluating the tensile and fracture properties from small volumes of material especially for assessing material degradation of structural components in service. In this paper, the existing methods to determine ultimate tensile strength (UTS) from small punch test are revisited and an improved method is proposed and validated through finite element analysis and experiments. In the new method, the force corresponding to the inflection point in the slope of force-deflection curve in the membrane stretching regime is identified for UTS correlation. The onset of plastic instability during small punch deformation is associated with this inflection point. The UTS correlation determined from the slope based method exhibited stronger linearity with lower relative error compared to the existing methods for a wide range of material strength and ductility. Highlights: The existing methods to estimate ultimate tensile strength (UTS) from small punch test are revisited. A new method based on slope changes of the load deflection curve in membrane stretching regime is proposed. The load identified for UTS correlation is linked to the onset of plastic instability. The load from slope based method correlated with UTS better than existing methods.